Su una nuova specie di Labrorostratus (Annelida Polychaeta) - Tenerelli, Vito (Bollettino delle Sedute Dell'Accademia Gioenia di Scienze Naturali in Catania., 1961)
The Author makes a description of a new species of Polychaete, Labrorostratus jonicus (Fam. Arabellidae) found amid the algae along the basaltic Coast of the Cyclopes Isles (Gulf of Catania). The genus Labrorostratus is new for the Mediterranean Sea, and the species herein described differs from L. parasiticus St. Jos. - the only one which has been known till nowadays - on account of the maxillary apparatus and the mandibles as well as for the presence of particular acicular setae.
World Polychaeta Database (WPolyD), article is not known to be online, except here